IMPACTS OF SAFETY INCENTIVE PROGRAMMES ON OCCUPATIONAL HEALTH AND SAFETY IN THE NIGERIAN OIL AND GAS INDUSTRY - Esitikot, E. L.; Obadimu, C. O. (American Journals, 2024)
The oil and gas industry is known to place high premium on safety because any unsafe condition may have severe consequences that may translate to several loses and damage to the environment. Apart from accidents that may lead to loss of work hours and payment of compensations, environmental damages arising from unsafe practices may cost the oil and gas company several millions of dollars to clean up. Hence proactive safety measures are usually recommended. To curb unsafe behaviours, safety incentives are used to modify workers’ behaviour to be more safety conscious by either rewarding safe behaviours and/or punishing unsafe behaviours. This study was carried out to ascertain if safety incentives promote proactive reporting of unsafe conditions among oil and gas industry workers in Nigeria as a means of enhancing their occupational health and safety.
Keywords: Effectiveness, Occupational Health, Proactive Reporting, Safety Incentives.